2018
DOI: 10.3847/1538-4357/aab616
|View full text |Cite
|
Sign up to set email alerts
|

Obscured Star Formation in the Host Galaxies of Superluminous Supernovae

Abstract: We present the results of 3 GHz radio continuum observations of the 8 host galaxies of superluminous supernovae (SLSNe) at 0.1 < z < 0.3 by using the Karl G. Jansky Very Large Array. Four host galaxies are detected significantly, and two of them are found to have high star-formation rates (SFRs > 20 M ⊙ yr −1 ) derived from radio emission, making them the most intensely star-forming host galaxies among SLSN host galaxies. We compare radio SFRs and optical SFRs, and find that three host galaxies have an excess … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 65 publications
3
25
0
1
Order By: Relevance
“…Here we report the VLA detection of an unresolved radio source coincident with the location of the SLSN PTF10hgi (z = 0.098; Inserra et al 2013;Perley et al 2016;De Cia et al 2018) about 7.5 years post-explosion. This represents the first detection of radio emission coincident with a known SLSN on any timescale (e.g., Coppejans et al 2018;Hatsukade et al 2018). We investigate the various possible origins of the radio emission -star formation activity, AGN, SN blastwave, and an off-axis jet -and show that none are likely, although in each scenario such an origin would represent an exciting and novel result.…”
Section: Introductionmentioning
confidence: 82%
“…Here we report the VLA detection of an unresolved radio source coincident with the location of the SLSN PTF10hgi (z = 0.098; Inserra et al 2013;Perley et al 2016;De Cia et al 2018) about 7.5 years post-explosion. This represents the first detection of radio emission coincident with a known SLSN on any timescale (e.g., Coppejans et al 2018;Hatsukade et al 2018). We investigate the various possible origins of the radio emission -star formation activity, AGN, SN blastwave, and an off-axis jet -and show that none are likely, although in each scenario such an origin would represent an exciting and novel result.…”
Section: Introductionmentioning
confidence: 82%
“…It is usually reported that superluminous supernovae are characterized by absolute luminosities at maximum light of MAB ≲ −21 mag, total radiated energies of the order of 10 51 erg [10] and a preference for low-metallicity, star-forming environments [11,12,13,14,15,16]. There are two broad classes: SLSNe II, which exhibit signatures of hydrogen in their optical spectra, and SLSNe I, which do not.…”
Section: -Superluminous Supernovaementioning
confidence: 99%
“…We selected the oldest ten SLSN-I from the first large sample with well-characterized host galaxies Schulze et al (2018). b Late-time radio limit at 3 GHz by Hatsukade et al (2018).…”
Section: Observationsmentioning
confidence: 99%